IN VITRO: ANTHELMINTIC ACTIVITY OF AQUEOUS LEAF EXTRACT OF Indigofera tintoria L AGAINTS Haemonchus contortus - W., SETYONO; KUSTANTINAH, KUSTANTINAH; YUSIATI, L. M.; SUWIGNYO, B.; NURCAHAYO, R. W. (Majalah Ilmiah Peternakan, 2024)
Gastrointestinal nematodes are one of the causes of reduced production efficiency in sheep and goats in Indone- sia, especially the Haemonchus contortus abomasum parasite. This parasite causes Haemonchosis disease which causes anemia and is fatal for productive sheep and goats. This study evaluated the inhibition of egg hatchability and mortality of adult H. contortus worms from in vitro infusaion of Indigofera tintoria L leaves. Indigofera leaf infusaion testing at five concentrations of 20%, 40%, 60% and 80%(w/v) was used both treatments. Albendazole at a dose 0f 2 mg/ml was used as apositive control, while negative control used 0.9% NaCl solution. At the highest concentration of 80% Indigofera leaf infusaion was able to inhibit egg hatching by 95.60% and had a mortality rate against adult H. contortus worms by 89.67%. The 80% concentration has the same effect when compared to the positive control using Albendazole. Phytochemical analysis of Indigofera tintoria L leaves contains condensed tannins and is useful as a bioanthelmintic.